Recent studies on the processes and formulation impacts in the development of solid dispersions by hot-melt extrusion - Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (European Journal of Pharmaceutics and Biopharmaceutics, 2021)
Industrial-scale pharmaceutical applications still face many challenges in overcoming the low absorption and bioavailability of poorly water-soluble drugs. Hot-melt extrusion has emerged as a promising approach with continuous processing on an industrial scale for the preparation of drug delivery systems. Many reviews have mentioned the potential applications, processes, principles and advantages and disadvantages of hot-melt extrusion in the pharmaceutical industry. However, a focus on the recent progress of hot-melt extrusion, which investigates the impacts of processes and formulations of solid dispersions of poorly water-soluble drugs, is missing. In this review, various factors, including polymers, drug properties, additives and surfactants, in solid dispersion SD formulations by hot-melt extrusion will be discussed. Moreover, the effects of the hot-melt extrusion process on the physicochemical properties of solid dispersions will be mentioned. The utilization of molecular interactions in hot-melt extrusion to improve drug stability will also be described. Overall, this summary of recent studies on solid dispersion by hot-melt extrusion will provide perspectives and effectiveness for the development of formulations containing poorly water-soluble drugs.
Keywords: Biological Availability; Chemistry, Pharmaceutical; Drug Compounding; Drug Delivery Systems; Drug Industry; Hot Temperature; Pharmaceutical Preparations; Polymers; Solubility; Hot-melt extrusion; Molecular interaction; Poorly water-soluble drugs; Solid dispersion; Stability